Internet connectivity disruption in Poland (Poland) - Voidly (Voidly Global Censorship Index, 2026)
CRITICAL severity disruption detected in Poland. Data sourced from IODA.
Network Disruption Incident ID: PL-2026-0004. Severity: critical. Confidence: 65%